Revealing the Social and Reproductive Health Dimensions Associated with Stunting among Children 6 – 23 months in Urban Areas of Indonesia - Dharminto, Dharminto; Agushybana, Farid; Nuridzin, Dion Zein; Winarni, Sri (Journal of Health Education, 2025)
Background: The prevalence of stunting in Indonesia has generally experienced a decline, although not significantly. The issue of stunting is not solely caused by a single, simple factor; rather, it is influenced by complex factors. This study aims to analyze the factors associating with stunting in urban areas across Indonesia. Methods: This study used a cross-sectional survey approach. The data were from the 2023 Indonesian Health Survey. The sample in this study were children aged 6 to 23 months residing in urban areas across Indonesia. Multiple logistic regression analysis was used to examine the associate between the independent variables and the dependent variable. Results: This study found that male (PR = 1.37), history of stunting at birth (PR = 1.41), low birth weight (PR = 2.13), history of tuberculosis (TB) (PR = 4.53) and family wealth status (PR = 2.28) were significantly associated with stunting status among children in urban areas. These factors were identified as key determinants, with their respective prevalence ratios indicating a substantial association with the prevalence of stunting in the population under study. Conclusions: In the urban context, there are predictive factors of stunting prevalence that require serious attention, such as having a history of TB illness and poor environmental health conditions